School Climate and its Relationship to Bullying among a Sample of middle School Students in Jeddah - Alsubia, Munerah Naif; Al-Ghamdi, Nawal GharmAllah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the relationship between the school climate and bullying among middle school students in Jeddah, in addition to identifying the differences in bullying among female students according to the changing grade (The first intermediate grade- the second- the third), and the social status of parents (Linked- separate- the death of one or both). Besides, the study aimed to identify the type of school climate and bullying behavior the most common among them. As a result, the sample of the study consisted of (201) students, and the researcher followed the descriptive correlation method, and the two study scales of the school climate and bullying (2020) were used by the researcher, and it was confirmed that the tool is characterized by honesty, consistency and its suitability for the sample. The results of the study concluded that there is a statistically significant correlation between the school climate and bullying. Also the existence of statistically significant differences in bullying due to the change of the school grade, and the absence of differences attributable to the change of the social status of parents. In addition, the study concluded that the most common school climate is the one that combines the characteristics of open and closed school climate. As for bullying, it is concluded that social bullying is the most common among female students, followed by physical bullying and verbal bullying, and finally bullying against the property. As a result of the findings of the study, the researcher reached a number of recommendations addressed to educational institutions to make the school environment suitable for acquiring and learning desired values and behaviors, and to reduce behavioral problems.